Contesting the two-component structural model of graphene oxide and reexamining the chemistry of graphene oxide in basic media. (November 2015) - Dimiev, Ayrat M.; Polson, Thomas A.
Abstract: The remaining ambiguity in the chemical structure of graphene oxide (GO) inspires new research, but also gives rise to numerous misconceptions that are based on the misinterpretation of experimental data. Recently, the two-component GO model was proposed and widely accepted by the scientific community. Here we discuss this model, demonstrate its insurmountable contradictions, and propose an alternative explanation for experimental observations that served as the model's foundation. We demonstrate that so-called oxidation debris, allegedly preexisting on all the GO samples, is in fact derived from GO during the strong-base-treatment. The base-treatment of aqueous GO solution hydrolyses organic sulfates and triggers a chain of reactions that result in C–C bond cleavage with the formation of ketones at newly formed edges. The ketones further transform into carboxylate ions. The ability of GO to delocalize and to accumulate a negative charge is a necessary condition and the driving force of these reactions. We stress that the absorbance band near 1620 cm −1 in GO FTIR spectra is originated by the bending modes of water molecules, but not by the CC bond stretch as commonly interpreted. Our findings provide new insights into GO chemistry, and reduce the confusion present in the modern GO field.